The essential role of annexin A1 mimetic peptide in the skin allograft survival - Teixeira, Rodrigo Antonio Parra; Mimura, Kallyne Kioko Oliveira; Araujo, Leandro Pires; Greco, Karin Vicente; Oliani, Sonia Maria [UNESP] (Hindawi, 2013)
Immunosuppressive drugs have a critical role in inhibiting tissue damage and allograft rejection.Studies have demonstrated the anti-inﬂ ammatory effects of the annexin A1 (AnxA1) in the regulationof transmigration and apoptosis of leucocytes. In the present study, an experimental skin allograftmodel was used to evaluate a potential protective effect of AnxA1 in transplantation survival. Micewere used for the skin allograft model and pharmacological treatments were carried out using eitherthe AnxA1 mimetic peptide Ac2-26, with or without cyclosporine A (CsA), starting 3 days beforesurgery until rejection. Graft survival, skin histopathology, leucocyte transmigration and expressionof AnxA1 and AnxA5 post-transplantation were analysed. Pharmacological treatment with Ac2-26increased skin allograft survival related with inhibition of neutrophil transmigration and inductionof apoptos is, thereby reducing the tissue damage compared with control animals. Moreover, AnxA1and AnxA5 expression increased after Ac2-26 treatment in neutrophils. Interestingly, thecombination of Ac2-26 and cyclosporine A showed similar survival of transplants when compared withthe cyclosporine A group, which could be attributed to a synergistic effect of both drugs. Investigationsin vitro revealed that cyclosporine A inhibited extracellular-signal-regulated kinase (ERK) phosphory-lation induced by Ac2-26 in neutrophils. Overall, the results suggest that AnxA1 has an essential role inaugmenting the survival of skin allograft, mainly owing to inhibition of neutrophil transmigration andenhancement of apoptosis. This effect may lead to the development of new therapeutic approachesrelevant to transplant rejection.
Keywords: annexin A1; cyclosporine A; neutrophils; skin; transplantation